The effect of anthropic pressures and elevation on the large and medium-sized terrestrial mammals of the subtropical mountain forests (Yungas) of NW Argentina - Di Bitetti, Mario Santiago (2013)
We conducted a 55-day long camera-trap survey in the Yungas subtropical forest in NW Argentina, to assess the effect of human accessibility, conservation status of the area, domestic animals and elevation on the diversity and composition of the large and medium-sized native terrestrial mammal assemblage. We deployed 24 camera-trap stations at distances of ∼2. km from each other. The study area is covered by continuous forest and has its center in the small community of Acambuco, in the Acambuco Provincial Reserve. The main economic activity in the area is oil/gas exploitation. Local residents raise cattle, hunt and use timber and non-timber forest products. The human impact was indirectly measured with an accessibility cost model. We used a multiple regression ANCOVA to assess the effect of elevation (range: 628-1170. masl), accessibility, protection status (reserve vs not) and frequency of records of domestic animals on the native mammal species richness and on a nonmetric multidimensional scaling (NMDS) ordination based on the frequency of records of the native mammals recorded at >3 camera-trap stations. We recorded 15 species of native mammals. Native mammal species richness decreased with elevation. Elevation was correlated with NMDS axes. Other predictive variables had no effect on species richness or the NMDS ordination, probably as a result of the relatively narrow range of conditions assessed in this study. The effect of elevation on mammal assemblages should be considered in landscape planning processes aimed at promoting biodiversity conservation. © 2012 Deutsche Gesellschaft für Säugetierkunde.